GP wellbeing during the COVID-19 pandemic: a systematic review - Jefferson, Laura; Golder, Su; Heathcote, Claire; Avila, Ana Castro; Dale, Veronica; Essex, Holly; van der Feltz Cornelis, Christina; McHugh, Elizabeth; Moe-Byrne, Thirimon; Bloor, Karen (British journal of general practice, 2022)
Doctors' organisations in the UK have reported worrying levels of work-related stress and burnout in the GP workforce for some time, and the COVID-19 pandemic has presented clear new challenges. To synthesise international evidence exploring the impact of COVID-19 on primary care doctors' mental health and wellbeing, and identify risk factors associated with their psychological wellbeing during this time. Mixed-methods systematic review. Six bibliographic databases, Google Scholar, and were searched on 19 November 2020 and 3 June 2021 to identify studies of GP psychological wellbeing during the pandemic. Reference checking was also conducted. Two reviewers selected studies, extracted data, and assessed the quality of studies using standardised tools. Heterogeneity in outcomes, setting, and design prohibited statistical pooling; studies were combined using a convergent integrated thematic synthesis. Thirty-one studies were included. Multiple sources of stress were identified including changed working practices; risk, exposure, and inadequate personal protective equipment (PPE); information overload; pandemic preparedness; and cohesion across sectors. Studies demonstrated an impact on psychological wellbeing, with some GPs experiencing stress, burnout, anxiety, depression, fear of COVID-19, lower job satisfaction, and physical symptoms. Studies reported gender and age differences: women GPs had poorer psychological outcomes across all domains, and older GPs reported greater stress and burnout. Use of outcome measures and reporting practice varied greatly. This review of international evidence demonstrates that the COVID-19 pandemic has adversely affected GPs' wellbeing around the world. Further research could explore gender and age differences, identifying interventions targeted to these groups.